Locus coeruleus and the defensive activation theory of rapid eye movement sleep: A mechanistic perspective - Knopper, Rasmus West; Hansen, Brian (Frontiers in Neuroscience, 2023)
The defensive activation theory (DAT) was recently proposed to explain the biological function of dreaming. Briefly, DAT states that dreams are primarily visual to prevent plastic take-over of an otherwise inactive visual cortex during sleep. Evidence to support the DAT revolve around the interplay between dream activity (REM%) and cortical plasticity found in evolutionary history, primate studies, and coinciding decline in human cortical plasticity and REM% with age. As the DAT may prove difficult to test experimentally, we investigate whether further support for the DAT can be found in the literature. Plasticity and REM sleep are closely linked to functions of the Locus Coeruleus (LC). We therefore review existing knowledge about the LC covering LC stability with age, and the role of the LC in the plasticity of the visual cortex. Recent studies show the LC to be more stable than previously believed and therefore, the LC likely supports the REM% and plasticity in the same manner throughout life. Based on this finding, we review the effect of aging on REM% and visual cortex plasticity. Here, we find that recent, weighty studies are not in complete agreement with the data originally provided as support for DAT. Results from these studies, however, are not in themselves irreconcilable with the DAT. Our findings therefore do not disprove the DAT. Importantly, we show that the LC is involved in all mechanisms central to the DAT. The LC may therefore provide an experimental window to further explore and test the DAT.